The Growth Of Highly Doped p-GaN On Sapphire By RF Plasma-Assisted Molecular Beam Epitaxy. - C, W Chin; Hassan, Z.; F, K Yam (2007)

(untitled)
In this paper, we present the study of the electrical, structural and optical properties of p-type GaN grown on sapphire by RF plasma-assisted molecular beam epitaxy (RF-MBE).